Polyphonic Thinking and the Divine - Kanaris, Jim. (Amsterdam : Editions Rodopi, 2013)
Philosophy of religion is a highly diversified field. An apt description of it is "zoo." It conjures imagery of a species-wide cacophony of sights and sounds. While some bemoan what this description implies, contributors to this volume appreciate it. There is no reason why a zoo should intimate a den of confusion rather than an important condition of emergence and novelty. "Polyphonic" is the catchall term to capture this sentiment. It signals a way of thinking that resists the desire to siphon insight into manageable packets of information in the name of historicality and finitude. A polyphon.
NINE Can We Continue to Use the Word "Religion" withImpunity?TEN On Relations without Relations: Religion, Literature, and Psychoanalysis in Julia Kristeva's Theory; ELEVEN Doing Philosophy of Religion as Glocal Losers; TWELVE Deictics: The Other as Quest; THIRTEEN Owing Life: Surviving Your Father; WRITINGS BY MAURICE BOUTIN; WORKS CITED; ABOUT THE CONTRIBUTORS; INDEX
Description based upon print version of record.
Keywords: Philosophy; Religion; Skepticism; Philosophy and religion; PHILOSOPHY / Methodology; Electronic books